Armament and History : A Study of the Influence of Armament on History from the Dawn of Classical Warfare to the Second World War - Fuller, J. F. C. (John Frederick Charles) (London Tyre & Spottiswoode, 1946)
Divided into armament epochs, this study looks at the influence of weaponry on history. Examining influential innovations in armament, and the leaders who employed them, the author attempts to show how advances in warfare have the potential to destroy civilization.
Include Index
Keywords: Military weapons